1994
DOI: 10.1002/j.1556-6676.1994.tb01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Among Native American Indian Youth: A Selected Review of Causality

Abstract: The author presents a selected review of substance use causality among Native American Indian youth. A review of selected empirical research relative to substance use is given. In addition, selected examples of research-oriented implications and practical suggestions are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…Similarly, about the same percentages of AIAN adolescents (ages 12-17 years) and those in other racial groups used alcohol in the past year, but AIAN adolescents were more likely to meet criteria for 12-month alcohol use disorder (7). In general, AIAN adolescents tend to have earlier onset of substance use than other ethnic groups (8)(9)(10) and to move more quickly into regular use (11)(12)(13)(14), resulting in earlier onset of substance use disorders (15).…”
Section: Substance Abuse In American Indian/alaska Native Communitiesmentioning
confidence: 99%
“…Similarly, about the same percentages of AIAN adolescents (ages 12-17 years) and those in other racial groups used alcohol in the past year, but AIAN adolescents were more likely to meet criteria for 12-month alcohol use disorder (7). In general, AIAN adolescents tend to have earlier onset of substance use than other ethnic groups (8)(9)(10) and to move more quickly into regular use (11)(12)(13)(14), resulting in earlier onset of substance use disorders (15).…”
Section: Substance Abuse In American Indian/alaska Native Communitiesmentioning
confidence: 99%
“…In one study, approximately one third of American Indian youth began to use alcohol by age 11 (Mail, 1995), and the average age at substance use initiation among American Indian youth is younger than what is found in other ethnic groups . Additionally, substance use among American Indian youth is associated with higher rates of lifetime alcohol use and alcohol misuse in comparison to European Americans or other ethnic minority groups (Herring, 1994). American Indian youth also have disproportionate rates of morbidity and mortality as a result of substance misuse.…”
Section: T He Use and Misuse Of Alcohol Is A Major Problem Among Youtmentioning
confidence: 99%
“…Griffin (2002) observed that the reinforcement of both individual and familial autonomy has resulted in a fragile sense of internal community identity and contributed to increased dissipation of traditional Traveller culture within greater social structures. Research indicates that indigenous groups with low reported drug use are those which are selectively acculturated, having adopted and merged both ethnic values with those of the dominant society (Oetting and Beauvais 1991, Herring 1994, Moran et al 1999, Brook and Pahl 2005. It appears that cultural traditions and practices can simultaneously facilitate drug use and promote abstinence (Brady 1995, James et al 1997, Felix-Ortiz et al 2001, Waller et al 2003).…”
Section: Discussionmentioning
confidence: 92%